Lithuanian Partisan Warfare in Museums during the Soviet Occupation and after the Restoration of Independence - Petrauskienė, Aistė (Lietuvos istorijos studijos, 2022)
The Lithuanian partisan war of 1944–1953 left many unanswered questions, which began to be examined more objectively in Lithuania after the restoration of independence. However, during the Soviet period, this topic also received a lot of attention, albeit from the Soviet propaganda side. The subject of the partisan war is defined rather narrowly in the museums of the Lithuanian SSR and independent Lithuania, but the context goes well beyond the issue of museum exhibitions and displays. Abundant archival documents provide a rather interesting picture and allow us to analyse not only the changes of the topic itself in museums in the Soviet system, during the Revival and in independent Lithuania, but also to show it as a struggle for memory. After the end of the partisan war, this topic was not eliminated from public life. Particular attention has been given to the reinterpretation of information. The shift from military to ideological propaganda was initially reflected in practical decisions. At a time when political life was undergoing the so-called ‘Khrushchev thaw’, propaganda gave particular attention to the interpretation of the legacy of the partisan war. The years 1957–1960 were a turning point in the formulation of further propaganda guidelines. During this period, the Museum of the Revolution of the Lithuanian SSR, in cooperation with the KGB structures, began to organise systematically expositions of the “crimes of the bourgeois nationalists” and exhibitions on the basis of the collected items. The introduction of a compulsory propagandistic idea of the “class struggle” during the Soviet era resulted in complex, largely emotion-based processes during the transition period. From the very beginning of the Sąjūdis, in the context of the partisan war. To refute the “class struggle” assessment established during the Soviet period, first of all, the construction of a narrative of the guerrilla war based on historical research was abandoned from the very beginning. The choice of a martyrological narrative, mainly based on empathy with the processes that took place in the past, has eventually shaped the narrative on victims in the museum exhibitions of independent Lithuania. As the generation of creators changed and young cultural workers took over the activities of the museums, and as experts in various fields were involved in the creation of the exhibitions, not only the forms of presenting the partisan war began to change, but also the content. It is centred not on fatalities, but on the determination to fight and defend the independence of the country.
Keywords: partisan warfare; museum; the Museum of the Revolution of the Lithuanian SSR; the Museum of Occupations and Freedom Fights